A cooperação penal internacional e a recuperação de ativos no exterior: avanços e desafios ao estado brasileiro à luz do combate internacional à lavagem de dinheiro - Medeiros, Ana Rosa de Brito (2012)
This dissertation is about the international cooperation in criminal matters and the international assets recovery. The overall analysis of the subject is focused on the reflection on how the brazilian state acts, specially when it comes to international cooperation on fighting against money laundering and its previous illegal acts. Due to the internationalization of private life, the nations noticed the importance of cooperating in order to guarantee its own sovereignty and the possibility to request diligences on other countries. With the view to improve this kind of cooperation, lots of nations became adopting a bunch of international instruments and, also, criminalizing several conducts (participation in a criminal organization, corruption, etc.), wishing to officialize the international cooperation against the money laundering. Nevertheless, many scholars believe that all the financial efforts involved in the recovery of the assets obtained with the money laundering are not worthy, as only a few of that assets are really recovered. After analyzing the money laundering dynamic, we talk a little about how all the government agencies act to fight against this illegal act, specially the Federal Police, the Office of the Attorney-General of the Union and the Council for Financial Activities Control. In order to fight off the money laundering was created, as well, the Department of Assets Recovery and International Legal Cooperation, the major authority in Brazil when it comes to international cooperation for assets recovery. Analyzing some collected data, we could notice that Brazil and USA had cooperated in some cases, but it´s important that the Brazilian state develop its skills of direct assistance, simplify its bureaucracy, amongst other challenges, in order to make the fight off against money laundering and the recovery of assets really effective.